THE ELBRUS CALDERA IN THE NORTHERN CAUCASUS: GEOLOGICAL STRUCTURE AND TIME OF FORMATION - Gurbanov A.G.; Bogatikov O.A.; Melekestsev I.V.; Lipman P.W.; Lowenstern J.B.; Miller D.R.; Dokuchaev A.Ya. (My University, 2004)
Complex field work in combination with the detailed interpretation of aerial and satellite photographs allowed us to discovered for the first time a large collapsed Elbrus Caldera (17×14 km along the edge of outer escarpment with a total area of ~230 km2).The Elbrus Volcano is located in its southern part. The mass ejecta of rhyodacitic and rhyolitic pyroclastics and the formation of the tuff and ignimbrite coves are related to the caldera formation. Time of the caldera origin, according U-Pb (SHRIMP) dating on zircon from fiamme of ignimbrites is between 689±30–722±15 Ka. Based on comprehensive investigation of the rocks of the Elbrus volcanic center, including K-Ar, 39Ar/40Ar and EPR dating of rock-forming quartz, we identified in its evolution precaldera, caldera and

postcaldera cycles. Two last cycles were subdivided into early and late stages.
Keywords: ELBRUS CALDERA; GEOLOGICAL STRUCTURE; TIME OF FORMATION